Tendencies of physical education development in ukraine at the beginning of XXI century - Dereka Tetiana (Borys Grinchenko Kyiv Metropolitan University, 2016)
The article defines and describes the trends of modern physical education in Ukraine. The features of physical education step training system forming were analyzed. The opportunities of continuous professional training educational programs improvement in basic, biomedical, psychologically-pedagogical and pedagogically sports-teaching blocks of disciplines were designated. The content of the educational process formation must necessarily take into account national traditions and customs through the introduction of ethnic and cultural components in the content of physical education. The teaching aids and computer technologies usage in the specialists' training educational process corresponds to real societal and social needs in a highly qualified competitive physical education specialists. An important part of the learning process and both a mean of direct feedback establishing between teacher and student are improving the control system of the physical education specialists' training educational process. There are peculiarities of the future specialist identity formation process and also his professional skills that will ensure his ability to lifelong professional learning and formation of his own motivation to achieving the acme characterized. Factors that enable professionals to succeed in the physical education profession such as: the ability to carry out educational activities; creativity; intellectual ability; professional orientation; personal qualities; external and internal factors (favorable educational environment, the strong personalities impact) were defined. There are terms of improving guidance and the selection of future professionals determined. The special attention is focused on improving the system of students' independent work and the transition to study at a research basis.